An Epidemic Recovery Framework to Jump-start Analysis, Planning, and Action on a Neglected Aspect of Global Health Security - Schoch-Spana, Monica (Clin Infect Dis, 2020)
Epidemic readiness and response command the disproportionate attention of health security decision makers, planners, and practitioners, overshadowing recovery. How patients and their families, health organizations, community sectors, and entire societies recuperate from major outbreaks requires more systematic study and better translation into policy and guidance. To help remedy this neglected aspect of health emergency management, we offer a working definition for epidemic recovery and a preliminary model of postepidemic recovery. Guiding this framework’s development are insights gleaned from the more mature study of postdisaster reconstruction and rehabilitation as well as recognition that postoutbreak recovery—which involves infectious disease, a biological hazard—presents challenges and opportunities distinct from events involving geological or meteorological hazards. Future work includes developing a consensus around characteristics of successful epidemic recovery, applying these metrics to support preincident planning for postepidemic recovery, and using such a scheme to track and inform actual recovery from an epidemic.